Economic forecasts, anchoring bias, and stock returns - Birz, Gene; Dutta, Sandip; Yu, Han (Financial Management, 2021)
By utilizing survey forecasts of macroeconomic statistics, we find that market participants’ expectations are not rational as they exhibit an anchoring bias. The forecasts systematically underpredict macroeconomic statistics and the forecast errors are predicted by past macroeconomic announcements. Most importantly, we find that the stock market does not see through this bias, that is, we find statistically significant stock price effects of “anticipated” components of macroeconomic announcements. Investors overweight the importance of historical information and do not make sufficient adjustments after the arrival of new information. © 2021 Financial Management Association International
Keywords: dept.fin; peer-reviewed